2010
DOI: 10.1111/j.1365-2958.2009.07012.x
|View full text |Cite
|
Sign up to set email alerts
|

The ribonucleases J1 and J2 are essential for growth and have independent roles in mRNA decay in Streptococcus pyogenes

Abstract: SummaryThe paralogous ribonucleases J1 and J2, recently identified in Bacillus subtilis, have both endoribonucleolytic and 5Ј-to-3Ј exoribonucleolytic activities and participate in degradation and regulatory processing of mRNA. RNases J1 and J2 have partially overlapping target specificities, but only RNase J1 is essential for B. subtilis growth. Because mRNA decay is important in regulation of virulence factors of Streptococcus pyogenes (the group A streptococcus, GAS), we investigated the role of these newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 36 publications
0
78
1
Order By: Relevance
“…S2A). This processing is probably carried out by RNases that were not included in this study, for instance RNases J1 or J2, which are essential for S. pyogenes survival [31]. We also cannot exclude that more than one RNase is capable of cleaving at this specific position ( i.e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2A). This processing is probably carried out by RNases that were not included in this study, for instance RNases J1 or J2, which are essential for S. pyogenes survival [31]. We also cannot exclude that more than one RNase is capable of cleaving at this specific position ( i.e .…”
Section: Resultsmentioning
confidence: 99%
“…secondary structures) in the mRNA 5′ UTRs [42]. However, other unidentified requirements, apart from the 5′ UTR, are also needed to discriminate the different sets of mRNAs to allow differential stability of virulence-related mRNAs [31]. RNase Y is involved in the regulation of virulence in S. pyogenes , but to date no regulatory mechanisms have been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…4 The group A Streptococci (GAS) also have two RNase J orthologs that play a role in mRNA turnover and, interestingly, both are essential. 28 A single non-essential RNase J ortholog has been identified in Sinorhizobium meliloti and has been shown to play a role in the maturation of the 5' end of 16S rRNA and both 23S rRNA fragments present in this organism. 29 This would suggest that rRNA maturation is not the essential function of RNase J1.…”
Section: Role Of Rnase J In Other Organismsmentioning
confidence: 99%
“…The group A Streptococci (GAS) also have two RNase J orthologs and, interestingly, both are essential (30). In this organism, differential mRNA stability is an important mechanism for the regulation of virulence factors.…”
Section: Global Effects On Mrna Metabolismmentioning
confidence: 99%
“…The degradation of both classes of mRNAs is affected in RNase J1 and J2 conditional mutants. It has been suggested that degradation of class II transcripts only occurs once RNases J1 and J2 are released from their primary task, degrading preferred class I mRNAs (30).…”
Section: Global Effects On Mrna Metabolismmentioning
confidence: 99%